Proceedings of the 2019 Conference on Empirical Methods in Natural Language Processing and the 9th International Joint Conferen 2019
DOI: 10.18653/v1/d19-1174
|View full text |Cite
|
Sign up to set email alerts
|

Multi-label Categorization of Accounts of Sexism using a Neural Framework

Abstract: Sexism, an injustice that subjects women and girls to enormous suffering, manifests in blatant as well as subtle ways. In the wake of growing documentation of experiences of sexism on the web, the automatic categorization of accounts of sexism has the potential to assist social scientists and policy makers in studying and countering sexism better. The existing work on sexism classification, which is different from sexism detection, has certain limitations in terms of the categories of sexism used and/or whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 31 publications
0
58
0
1
Order By: Relevance
“…Sharifirad and Jacovi [38] presented a categorization of sexism that included indirect, sexual, and physical sexism. A more recent study by [39] seeks to categorize accounts of sexism. Because the growing interest of hate detection towards women, other tasks to protect women from hate on the internet have emerged.…”
Section: B Misogyny Detectionmentioning
confidence: 99%
“…Sharifirad and Jacovi [38] presented a categorization of sexism that included indirect, sexual, and physical sexism. A more recent study by [39] seeks to categorize accounts of sexism. Because the growing interest of hate detection towards women, other tasks to protect women from hate on the internet have emerged.…”
Section: B Misogyny Detectionmentioning
confidence: 99%
“…Topic modeling is a popular text mining technique to identify hidden semantic structure of corpora (Karami, 2015) and has been used for a wide range of applications such as analyzing social media data (Shaw & Karami, 2017; Karami, Dahl, Turner‐McGrievy, Kharrazi, & Shaw, 2018; Webb, Karami, & Kitzie, 2018; Karami, Webb, & Kitzie, 2018; Karami & Shaw, 2019), opinion mining (Hemsley, Erickson, Jarrahi, & Karami, 2020; Karami, Bennett, & He, 2018; Karami & Elkouri, 2019; Karami & Pendergraft, 2018; Karami, Shah, Vaezi, & Bansal, 2020), literature reviews (Karami, Lundy, Webb, & Dwivedi, 2020; Shin et al, 2019), spam detection (Karami & Zhou, 2014a), investigating social media strategies (Collins & Karami, 2018; Karami & Collins, 2018), and exploring medical and health documents (Karami & Gangopadhyay, 2014; Karami, Gangopadhyay, Zhou, & Kharrazi, 2015a, 2015b; Karami, Gangopadhyay, Zhou, & Kharrazi, 2018; Karami, Ghasemi, Sen, Moraes, & Shah, 2019). Closer to our work is a study that analyzed short‐length stories on the everyday sexism project website to classify sexual harassments to 14 categories (e.g., body shaming, rape, and threats) (Parikh et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…However, recent research has shown important sub-classifications of sexism that may be important for online media research. (Parikh et al, 2019) classifies tweets into 14 sub categories of sexism and we identify that not all 14 categories may have as drastic effects as victim blaming and slut shaming. Victim Blaming on online media directly leads to psychological disturbances for the victim and biased responses from authorities seeking legal action for such crimes (Gruenewald et al, 2004).…”
Section: Motivation: Weibo Victim Scandalmentioning
confidence: 99%